2019
DOI: 10.3390/nu11061225
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects and Mechanisms of Garlic on Dyslipidemia and Gut Microbiome Dysbiosis

Abstract: Garlic (Allium sativum L.) contains prebiotic components, fructans, antibacterial compounds, and organosulfur compounds. The complex ingredients of garlic seem to impart a paradoxical result on the gut microbiome. In this study, we used a mouse model to clarify the effects of whole garlic on the gut microbiome. C57BL/6N male mice were fed with or without whole garlic in normal diet (ND) or in high-fat diet (HFD) for 12 weeks. Supplementation with whole garlic attenuated HFD-enhanced ratio of serum GPT/GOT (glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 59 publications
4
42
1
1
Order By: Relevance
“…We found that whole garlic and AFG had the same tendency to inhibit the ratio of GPT to GOT caused by HFD. Although we found that whole garlic inhibited the HFD-induced increases of TG and LDL [23], AFG had no significant effect on lipid metabolism in this study. These data suggested that the garlic OSCs played an important role in improvement of HFD-induced dyslipidemia.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…We found that whole garlic and AFG had the same tendency to inhibit the ratio of GPT to GOT caused by HFD. Although we found that whole garlic inhibited the HFD-induced increases of TG and LDL [23], AFG had no significant effect on lipid metabolism in this study. These data suggested that the garlic OSCs played an important role in improvement of HFD-induced dyslipidemia.…”
Section: Discussioncontrasting
confidence: 83%
“…These data suggested that the garlic OSCs played an important role in improvement of HFD-induced dyslipidemia. On the other hand, although both of the whole garlic [23] and AFG increased the relative abundance of f-Lachnospiraceae, g-Akkermansia, and g-Lactobacillus, AFG showed down-regulation of the diversity of gut bacteria, and whole garlic [23] showed up-regulation of the diversity of gut bacteria. It is possible that this is due to the interaction effect of garlic OSCs and fructans on gut microbiome, although the reason is still unknown.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Previous reports have reported the cardiovascular effects of garlic including potentially irreversible antiplatelet activity, anticoagulant, fibrinolytic activity, a remarkable decrease in platelet accumulation and mixed activity on fibrinolytic effectiveness [130]. Chen et al [131] revealed that dehydrated raw garlic powder when administered orally resulted in acute injury to the gastric mucosa, whilst Yuncu et al [132] reported that AGE, the sulfur-free compound, protects the intestinal mucosa of experimental animals. Clinical studies reported that low doses of garlic are safe, whereas therapeutic doses might cause mild gastrointestinal disorders, while high doses have been reported to cause liver damage [82,123,133].…”
Section: Adverse Effects and Toxicitymentioning
confidence: 99%